(3jhe aWGFQ GdYSds - (3LQjaR, Shs; (3eWdb, CdHjQs ((3HjQhJs (3ecJHI dHfGf fGTQhfs, 2010)
(3Ce djdi eQjVI , djdi hCHhgG jQjOGf EYGOI GdGHJSGeI Edi hLggG , cja ? QHeG HEYOGO GdMdhi GdeaVdI dOjgG , GdaWGFQ HGdYSds
(3bUU YQHjIs
(3GdfU eJQLe ef GdEfLdjRjI Edi GdYQHjIs
Keywords: Arabic stories; (3GdbUU GdYQHjIs; (3bUU hMcGjGJs